NOUNS IN ENGLISH – STRUCTURE, THEORY, LINGUISTIC RESEARCH, AND SCHOLARLY PERSPECTIVES - Inoyatulloyeva Nazokat Izzatullo qizi (TADQIQOTLAR, 2026)
Annotation: This article provides a comprehensive and scholarly examination of nouns in English, exploring their structure, historical development, classifications, linguistic functions, and cognitive significance. It highlights theoretical perspectives from leading linguists, including Chomsky, Crystal, Aitchison, Jespersen, and Huddleston, demonstrating how nouns serve as core lexical categories, semantic anchors, and essential components of communication. The study also discusses irregular plurals, noun phrases, and the role of nouns in academic and cognitive development. Emphasis is placed on the interaction between grammatical structure and human cognition, showing that nouns not only label the world but also shape how knowledge is organized and conveyed. This article underscores the centrality of nouns in English language structure, research writing, and formal communication.